The effect of long-term soccer training on left ventricular structure and function in elite male youth soccer players - Unnithan, V. B.; Beaumont, A.; Rowland, T.; George, K.; Stewart, L.; Sculthorpe, N.; Lord, R. N.; Oxborough, D. L. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Aims Cardiac adaptations in elite, male adolescent youth soccer players have been demonstrated in relation to training status. The time course of these adaptations and the delineation of the influence of volatile growth phases from the training effect on these adaptations remain unclear. Consequently, the aims of the study were to evaluate the impact of 3 years of elite-level soccer training on changes in left ventricular (LV) structure and function in a group of highly trained elite youth male soccer players (SP) as they transitioned through the pre-to-adolescent phase of their growth.